Pelatihan Tentang Public Speaking dan Keterampilan Pranata Adicara dengan Pengantar Bahasa Jawa fi Pedukuhan Somodaran, Desa Banyuraden, Gamping, Sleman - Unggul Priyadi; Nursya'bani Purnama (Asian Journal of Innovation and Entrepreneurship, 2018)
Indonesia is a multicultural country rich in culture. One culture that still is in the form of tradition mantenan sustainable or traditional Javanese wedding. During the procession of events taking place mantenan language using the Java language. In supporting the smooth and successful series of wedding procession that is so sacred, one of the driving forces is the role of organizers (MC) which uses the Java language introduction adicara institutions. The desire of people RT-03 Pedukuhan Somodaran, Banyuraden village to preserve the traditional wedding ceremony Yogyakarta, the main attraction. However, the village is still shortage of professionals in performing marriage ceremonies Yogyakarta. One reason is the lack of knowledge and understanding of the custom wedding procession Yogyakarta is still low. In addition, the human resources that can act as guides and teaching institution with an intermediary adicara Java language still small in number.In this study objectives to be achieved are: improving public speaking skills and have the ability as an intermediary institution with the Java language adicara need a comprehensive effort. One alternative that is done is a method of skills development and training in public speaking skills intermediary institutions adicara with the Java language. Participants will be given training to be pranacara various wedding events, namely: pranacara application, peningsetan adicara institutions, institutions adicara consent, midodareni adicara institutions, and institutions adicara Panggih. The method used is setting the example by instructors and practice directly by the participants.Some of the findings in the training process are: supporting the smooth and successful series of wedding procession that is so sacred, one penunjangnnya is the role of organizers (MC) which uses the Java language introduction adicara institutions. In addition to the welcome speeches from both candidates keluaraga groom and women (public speaking) using the Java language supporting the ongoing success of the wedding procession. After training and simulation, public confidence in Somodaran hamlet, village Banyurade will gradually increase and also the increase in professionals as MC in the event mantenan. The public will learn to plan, create structure and practice of bringing the event in front of an audience. The training is designed with an informal atmosphere and the risk-free personal feedback where needed on each individual to know the obstacles faced when he became institutions adicara (MC) with intermediate Java language.